(untitled) (Hoboken, NJ, 2017)
The rapidly evolving language-technology interface has propelled dramatic changes in, and increased opportunities for, second language teaching and learning. Its influence has been felt no less keenly in the approaches and methods of assessing learners' language and researching language teaching and learning.
Keywords: Language and languages,Ngôn ngữ và ngôn ngữ; Study and teaching,Technological innovations.,Hướng dẫn sử dụng máy tính.